The Problem of Tolerance in the Context of Globalization - Pirumyan, Tatevik (Bulletin of Yerevan University E: Philosophy, Psychology, 2013)
Current globalization processes of contemporary world cultures approach not only each other and integrate into each other but also disengage and disintegrate. In this context the article analyzes tolerance as an important and necessary paradigm of coexistence. The article presents four main manifestations of tolerance: tolerance towards other viewpoints; equality of all cultures and cognitive orientations; tolerance toards metaphysical, religious and ideological alternatives; respect for other viewpoints.